How low can you go? Exploring impact of drones on haul out behaviour of harbour - and grey seals - Stepien, Emilie Nicoline; Khan, Jibran; Galatius, Anders; Teilmann, Jonas (Frontiers in Marine Science, 2024)
Introduction Drones, or Unmanned Aerial Vehicles (UAVs), have emerged as valuable tools for wildlife monitoring, offering potentially non-intrusive observations in challenging terrains like marine ecosystems. Despite their potential, widespread use is impeded by regulatory constraints, especially in protected areas. Methods This study aims to assess the impact of varying flight altitudes and flight approaches of two commercial drones on the behaviour of harbour seals (Phoca vitulina) and grey seals (Halichoerus grypus) and compare to existing findings for marine mammals. We conducted a comparative analysis of the response to flight altitude from 70 m gradually descending to 10 m and two different flight approaches between the DJI Phantom 4Pro and the Autel EVO II RTK drones in the Danish part of the Wadden Sea. Results We found varying responses, where species-specific sensitivity and environmental conditions appeared to influence the behavioural reactions of the seals. Our results reveal that seal reactions to drones are complex and depend on several factors, such as flight altitude, drone model, received noise levels, approach, weather conditions, the animals’ annual cycle, and geographic location. Discussion The outcomes hold significance for refining regulatory policies governing drone flights in protected marine environments, balancing conservation efforts with technological advancements in wildlife monitoring and ensuring undisturbed observations of seals.